2015
DOI: 10.3923/ajar.2015.189.207
|View full text |Cite
|
Sign up to set email alerts
|

Melittophilous Mode of Pollination Predominates in European Plum (Prunus domestica L.) in the Semi-Arid Environment of Northwest India

Abstract: European plum (Prunus domestica L.) is an important fruit and medicinal plant. This fruit plant is a new introduction in the Northwest region of India. Flowers of this plant need crosspollination for fruit set. However, the spectrum of pollinators and their relative role in pollination of flowers of this fruit plant in this region is not known. To meet these objectives, the present study was carried out. An entire range of flower visitors of this fruit plant was captured with hand net from its field and were i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 29 publications
2
8
0
Order By: Relevance
“…The honey bees were the predominant visitors of the flowers of Aonla in the semi-arid environment of Northwest India. These results resemble the results of other studies carried out in this region [4][5][6][7][8][9][10]. The pollinators made preferably more visits on male flowers than female flowers (Fig.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…The honey bees were the predominant visitors of the flowers of Aonla in the semi-arid environment of Northwest India. These results resemble the results of other studies carried out in this region [4][5][6][7][8][9][10]. The pollinators made preferably more visits on male flowers than female flowers (Fig.…”
Section: Discussionsupporting
confidence: 89%
“…and a butterfly (Psichotoe duvauceli) were the non-dominant visitors and were clubbed under "other insect pollinators." Similar pattern of insect diversity was observed in the earlier studies carried out in the semi-arid environment of Northwest India [4][5][6][7][8][9][10].…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…In the semi-arid environment of northwest India, the red dwarf honey bee (Apis florea) visited some 38 locally grown crops and acted as an important pollinator of more than 35 of these crops (Table 1). In earlier studies too, this honey bee was identified as the most abundant flower visitor of many crop plants in the semi-arid environment of northwest India 1,[17][18][19][20][21][22][23][24][25][26][27][28][29] . In this part of India, the Indian hive bee (Apis cerana) is not indigenous and managed pollination with Apis mellifera has not yet practiced on large scale.…”
Section: Discussionmentioning
confidence: 99%
“…botrytis) 19 , carrot (Daucus carota L.) 20,21 , coriander (Corriandrum sativum L.) 22 , fennel (Foeniculum vulgare L.) 21,23 , Cucumber (Cucumis sativus L.) 24 , Praecitrullus (Praecitrullus fistulosus) 25 , wanga (Cucumis melo s.sp. melo) 26 , Onion (Allium cepa L.) 21,27 , sarpagandha (Rauvolfia serpentina) 28 and European plum (Prunus domestica L.) 29 . However, this report is not exhaustive.…”
Section: Introductionmentioning
confidence: 99%